Springboard and platform diving - Huber, Jeffrey J., 1953- (Champaign, IL : Human Kinetics, 2016)
Authored by US Olympic diving coach and US National Coach of the Year. Deconstructs the various phases of each dive and provides expert insights, instructions, and drills for each phase
How coaches teach, how divers learn -- Forward approaches -- Backward presses -- Take-offs and connections -- Positions, spotting, and come-outs -- Line-ups and entries -- Skill progression: Putting it all together -- Strength, conditioning, nutrition, and recovery -- Creating an annual individualized training plan -- Mental training for practice -- Mental training for competition
Includes bibliographical references and index.
Keywords: Springboard diving; Diving